INTERNALIZATION OF RELIGIOUS EDUCATION VALUES IN ENHANCING TOLERANCE AMONG RELIGIOUS COMMUNITIES - Kharisma, Ivan; Aisyah, Nur; Qodriyah, Khodijatul; Agus R, Abu Hasan; Sugiono, Sugiono (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to delve into and describe the process of internalizing the values of Religious Education in enhancing tolerance among religious communities at SMPN 2 Sukasada. Using a qualitative approach, this study employs a qualitative descriptive method by collecting data through observation, interviews, and documentation. SMPN 2 Sukasada, Bali, was chosen as the research location, and the informants included the School Principal, Hindu Religious Education Teachers, and Islamic Religious Education Teachers. The process of internalizing the values of Religious Education is carried out through the teachers' role modeling, instilling a coexistence attitude, promoting good morals, and supporting activities such as flag ceremonies and religious celebrations. The research findings indicate that the internalization process of Religious Education values at SMPN 2 Sukasada reaches the stage of value transactions, where teachers engage in exemplification, habituation, and motivation to instill a tolerant attitude. Despite internalization efforts, challenges arise from spiritual teachers outside the school who use intolerant language, potentially leading to conflicts of intolerance. Students' understanding of culture is also limited, as seen in misunderstandings about traditional Balinese attire, which is considered specific to Hindus during prayer. Thus, this research emphasizes the importance of the internalization process of Religious Education values in the context of religious tolerance in schools, while also highlighting the need for a better understanding of culture and religious teachings as a preventive measure against intolerance. The school's Pancasila Student Profile Strengthening Program (P5) is also presented as an alternative to connect Religious Education with social and cultural life in Bali.